2012
DOI: 10.2298/abs1202471c
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and Ω3/Ω6 ratios of the muscle lipids of six fish species in Sugla Lake, Turkey

Abstract: Fatty acid composition of the muscle lipids of Carassius gibelio, Pseudophoxinus anatolicus, Sander lucioperca, Tinca tinca, Vimba vimba tenella and Capoeta capoeta in Sugla Lake were determined. In all species, palmitic acid (13.25- 18.54% of total fatty acids) and oleic acid (11.93-34.23% of total fatty acids) were identified as major saturated fatty acid (SFA) and monounsaturated fatty acid (MUFA), respectively. Docosahexaenoic acid (DHA) was found to be the major polyunsaturated fatty acid (PUFA) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
3
7
0
1
Order By: Relevance
“…Many studies from the fish living in freshwater systems revealed that C16:0 and C18:0 were the main components of the saturated fatty acids (SFAs) (Uysal et al, 2006;Guler et al, 2007;Cakmak et al, 2012;Görgün and Akpınar, 2012). The present study also found C16:0 and C18:0 to be the primary fatty acids of SFAs in the V. vimba tissues.…”
Section: Fatty Acid Composition Of Total Lipidmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies from the fish living in freshwater systems revealed that C16:0 and C18:0 were the main components of the saturated fatty acids (SFAs) (Uysal et al, 2006;Guler et al, 2007;Cakmak et al, 2012;Görgün and Akpınar, 2012). The present study also found C16:0 and C18:0 to be the primary fatty acids of SFAs in the V. vimba tissues.…”
Section: Fatty Acid Composition Of Total Lipidmentioning
confidence: 99%
“…Kalyoncu et al (2009) reported similar results in the muscle of V. vimba, in which MUFA levels were found to be higher than PUFAs and SFAs in all seasons investigated. At the same time, Cakmak et al (2012) emphasized that V. vimba was a fish species rich in MUFAs when compared to fish species such as Sander lucioperca, Capoeta capoeta, and Pseudophoxinus anatolicus. The data obtained in the present study on the MUFA levels in different tissues of V. vimba seem Table 1.…”
Section: Fatty Acid Composition Of Total Lipidmentioning
confidence: 99%
See 1 more Smart Citation
“…Their PUFA quantity is amazingly high which ranges from 6.9 to 18.3% (Dey et al, 2015). Another study by Nath et al (2014) has also confirmed these findings, But Cakmak et al (2012) Identified 38 fatty acids from the wild fresh water fish species from Sugla Lake, Turkey. These Turkish fresh water fish species has less quantity of SFAs (21.43 to 21.36 to 26.33%) as compared to Pakistan fish species 48.5-65.7%).…”
Section: Fatty Acids Profilementioning
confidence: 83%
“…The amount of lipids and fatty acid composition in fish is known to be influenced by various factors in different species or within a species, such as geographical region, season, feeding habits and diet, age, sex, spawning period etc. Total lipid and fatty acid composition data are important for nutritionists and food scientists; to help them in dietary formulations, nutrient labeling, processing and (Moreira et al, 2001;Haliloğlu et al, 2004;Özyurt et al, 2007;Özoğul et al, 2007;Thammapat et al, 2010;Özden, 2010;Köse et al, 2010;Tufan et al, 2011;Jahkar et al, 2012;Çakmak et al, 2012). Lake Van is the fourth largest terminal and the largest soda lake on earth with the surface area 3574km 2 , total volume 607km 3 and maximum depth 450m, and it is the largest lake of Turkey.…”
Section: Introductionmentioning
confidence: 99%